Insight into the biochemical and physiological mechanisms of nanoparticles-induced arsenic tolerance in bamboo - Emamverdian, Abolghassem; Ding, Yulong; Hasanuzzaman, Mirza; Barker, James; Liu, Guohua; Li, Yang; Mokhberdoran, Farzad (Frontiers in Plant Science, 2023)
Arsenic contamination in soil, sediments, and water poses a significant threat to the growth of bamboo plants. Hence, an in vitro experiment has been conducted to determine the influence of three types of nanoparticles: 150 µM silicon nanoparticles (SiO2 NPS), 150 µM titanium nanoparticles (TiO2 NPs), and 150 µM zinc oxide nanoparticles (ZnO NPs) on enhancing arsenic (As) (150 µM and 250 µM) toxicity tolerance in 1-year-old bamboo species (Pleioblastus pygmaeus). The results showed that nanoparticles increase antioxidant and glyoxalase system activity, ascorbic acid, glutathione, phytochelatin, proline, sugar and photosynthesis pigment content, as well as plant growth and development. This is achieved by reducing reactive oxygen species (ROS) components, electrolyte leakage (EL), malondialdehyde (MDA), hydrogen peroxide (H2O2) and the superoxide radical (O2•−), as well as arsenic (As) accumulation in plant organs. The ZnO NPs, SiO2NPs, and TiO2NPS alone and in combination significantly increase plant tolerance to As toxicity via key mechanisms, including stimulation of antioxidants’ activity and glyoxalase defense systems to scavenging of ROS and methylglyoxal (MG), improvement of the phytochelatin metabolism, reduction of metal accumulation and translocation, and improvement of photosynthesis pigments in plants under As toxicity. We can conclude that the combination of 150 µM ZnO NPs, SiO2 NPs, and TiO2 NPs has the greatest effect on enhancing plant tolerance to 150 µM and 250 µM arsenic.